Physical exercise as a strategy for reducing social anxiety in young adults: a review of the evidence - Knapik, Anna; Stadnicka, Olga; Brodowska, Anna; Kuś, Justyna; Zięba, Natalia; Czapiński, Olgierd; Tomicka, Ewa; Ciesielski, Maciej; Pysiewicz, Mateusz; Białowąs, Patrycja (Quality in Sport, 2026)
Background: Social anxiety disorder constitutes one of the most prevalent anxiety disorders among young adults and is associated with marked impairments in quality of life and social functioning. In recent years, increasing scientific interest has been directed toward non-pharmacological interventions that may complement conventional treatment approaches, particularly physical activity. Aim: This study aims to evaluate the impact of physical activity on reducing symptoms of social anxiety in young adults and to identify potential underlying mechanisms. Materials and Methods: A narrative review of the scientific literature was conducted, focusing on studies examining the relationship between physical activity and social anxiety symptoms. Observational and experimental studies, as well as systematic reviews published in peer-reviewed journals, were included. Results: The literature indicates that regular physical activity may alleviate symptoms of social anxiety. These effects are associated with both psychological mechanisms (e.g., improved self-esteem, social exposure) and biological processes (e.g., neurotransmitter regulation, stress reduction). Conclusions: Physical activity appears to be a promising adjunctive approach for reducing social anxiety symptoms in young adults. Nevertheless, further research is needed to determine its optimal type and intensity.